1970
DOI: 10.3126/on.v8i1.4308
|View full text |Cite
|
Sign up to set email alerts
|

Production of Surface Active Glycolipid by Serratia marcescens NSK-1 Isolated from Petroleum Contaminated Soil

Abstract: Biosurfactant-producing Serratia marcescens NSK-1 strain was isolated from soil contaminated with petroleum products. The organism, when grown in mineral salts medium with sucrose as sole carbon source, produced a surface-active anthrone-positive glycolipid. The biosurfactant was partially purified by liquid-liquid partition chromatography in chloroform-methanol mixture (1:1) and silica gel chromatography. It reduced the surface tension of distilled water from 72 dynes/cm to 40 dynes/cm and exhibited good emul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Park et al (2006) reported that LD 50 of surfactin in mice was above 2 g/kg. Biosurfactant produced by Serratia marcescens was administered to the mice orally at the dose of 5 g/kg and no toxic effect was noticed in the mice (Anyanwu et al, 2011). The available reports evidenced that lipopeptide and rhamnolipid biosurfactants in general were non-toxic biomolecules which can be used as food additives.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al (2006) reported that LD 50 of surfactin in mice was above 2 g/kg. Biosurfactant produced by Serratia marcescens was administered to the mice orally at the dose of 5 g/kg and no toxic effect was noticed in the mice (Anyanwu et al, 2011). The available reports evidenced that lipopeptide and rhamnolipid biosurfactants in general were non-toxic biomolecules which can be used as food additives.…”
Section: Resultsmentioning
confidence: 99%
“…The biosurfactant SR 122 solution (0.7% w/v) was adjusted to different pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The activity of the biosurfactant SR 122 was measured at each pH value by using the ODA method.…”
Section: -2 Effect Of Different Ph Valuesmentioning
confidence: 99%
“…These potent surface-active agents contain hydrophobic (unsaturated or saturated fatty acids) and hydrophilic (amino acids or peptides; mono, di or polysaccharides) moieties that reduce surface tension and interfacial tension between individual molecules at the surface and the interface of the immiscible liquids (Makkar et al 2011;Vignesh et al 2011). Biosurfactants thereby expedite the degradation of hydrocarbons by enhancing their diffusion into the bacterial cell via dispersion and/or emulsification (Anyanwu et al 2011). …”
Section: Surface-active Compoundsmentioning
confidence: 99%